IMPLEMENTASI METODE PEMBAYARAN CASHLESS DI UMKM DESA PAYA GELI: TREN, TANTANGAN, DAN DAMPAKNYA - Chuzaimah Batubara; Layyinatus Shifah (Kampus Akademik Publiser, 2024)
This research discusses the utilization of cashless payment methods in Micro, Small, and Medium Enterprises (UMKM) in Payageli Village, focusing on implementation, challenges, and impacts. The study employed a qualitative research method with a descriptive approach and literacy method. Data were gathered through observation, documentation, and interviews with UMKM business owners in the village. Findings indicate a growing trend in the use of cashless payment methods in Indonesia, particularly among the younger generation. Bank Indonesia has taken steps to facilitate non-cash transactions. Cashless or cardless transaction behavior has been present in Indonesia since 2007 but has not yet reached its full potential. The use of e-money and QRIS is becoming more popular, facilitating digital transactions. The benefits of digital transactions include convenience, security, efficiency, and discounts. Despite challenges such as social disparities and poor internet connectivity, the use of QRIS in Paya Geli Village is already popular and advantageous for UMKM business owners.